Desarrollo de una metodología práctica para la aplicación de la Norma Internacional de Información Financiera N°1 Adopción por primera vez de las normas internacionales de información financiera en la empresa Grinsa SRL. - Rodriguez Vargas, Elisa Lisbeth (2013)
The present work is to investigate, to analyze and describe a practical methodology for implementing the International Financial Reporting Standard No. 1 in the company Grinsa SRL. To fulfill this purpose raised the following specific objectives: - Identify the rules governing the implementation of IFRS 1 - Apply IFRS 1 GRINSA SRL Construction Company, which is an appropriate point of departure for all IFRS accounting. - Initial conversion of the financial statements of the company GRINSA SRL with the application of IFRS 1 This study is classified as descriptive explanatory in that it has a current situation, with its variables and analyzes. It was based on primary sources as was the financial staff of the company under study, who were applied to indepth interview and secondary as financial and administrative organization. The main results show that the company GRINSA SRL, adjusted to comply with the international financial reporting standards in accordance with the provisions of the objectives of the parent company.